Práticas com smartphones para idosos - Um projeto de extensão do ICMC/USP - Rodrigues, Kamila R. H.; Santos, Suzane S. dos; Gallego, Daniele; Martins, Ketlen; Malpartida, Katherin F. C.; Verhalen, Aline E. C.; Deus, João Pedro de (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
This paper describes the structure and methodology of a digital literacy program for the elderly, which has been operating since 2015 as part of a university extension project, with essential results for the surrounding community. The use of a methodology that adds the adoption of a computational solution to carry out remote interventions facilitated teaching and learning for elderly students. Classes that take place every six months at ICMC/USP demonstrated the relevance of digital literacy programs for the elderly. This paper brings reports of the course methodology, as reports from some elderly students and monitors about the same.